Antisense Therapy - Sharad, Shashwat; Kapur, Suman (IntechOpen, 2019)
Antisense Therapy offers a comprehensive, state-of-the art perspective on the role of antisense therapy in the treatment of human disease, with a special focus on cancer. Use of antisense oligonucleotides is a growing field of pharmaceutical and biotech companies and research programs for treatment of several diseases. This book summarizes and presents the best updates, therapeutic principles, methods, and applications in the field and offers meaningful information to move treatment discovery forward.